The Implementation of English Podcast in Enhancing Students' Speaking Skills For Eleventh Grade Students - Islami, Fernandita (RETAIN, 2021)
This study aimed to find out whether the implementation of English podcast in teaching and learning can enhance students’ speaking skill especially in pronunciation, grammar, vocabulary, fluency, and comprehension. There were 36 eleventh grade students from SMAN 3 Surabaya in the academic year 2020/2021 as the sample. The group was given pre-test and post-test. To collect the data, speaking tests were administered to students. The obtained data were analyzed by using paired sample t-tests. The result showed that the implementation of English podcast could enhance students’ speaking skills in eleventh grade students. SPSS Statistics was used to analyze the data, specifically by using paired sample test. The mean score of post-test was (86.33), which was higher than the mean score of pre-test (64.44). The t-test score was -24.478 and the degree of freedom (df) was 35. Accordingly, podcast was an effective and innovative technology-based learning tool in English classroom, especially in integrating speaking. Keywords: podcast, speaking skills, technology.